PEMBERDAYAAN MASYARAKATBERBASIS DESA WISATA (STUDI KASUS DI DESA WISATA KADISOBO II, DESA TRIMULYO,KECAMATAN SLEMAN) - Dwiyanti Destiningrum; Nanik Dara Senjawati; Eko Murdiyanto (Jurnal Dinamika Sosial Ekonomi, 2018)
Nowadays the optimization of a village began to be done by turning ordinaryvillage into a tourism village where the development of tourism in the village isnot separated from the characteristics of existing community activities, botheconomic and socio-cultural aspects and utilized as much as possible for thewelfare of the people. This study aims to examine the process of communityempowerment and analyze group dynamics in Tourism Village Kadisobo II. Themethod used in this research is qualitative approach with a case study in TourismVillage Kadisobo II. The subjects of the study were Head of Dusun, chairman andmanagement of POKDARWIS, head of POKDARWIS sub group. Data collectionis conducted by observation, interview, and documentation. Validity of data in thisstudy using triangulation. Data analysis is done by domain analysis and datareduction. Based on the results of research, a) the process of communityempowerment in Desa Wisata Kadisobo II through three stages, the first is theawareness, the Second is the capacity building, and the third stage is theempowerment that fosters community empowerment. b) Group dynamics takesplace in the community empowerment process of Kadisobo II Tourism Village. The stage of group development in Desa Wisata Kadisobo II is at the normingstage towards performing. Keywords: community empowerment, group dynamics, tourism village